2018
DOI: 10.1186/s41235-018-0135-2
|View full text |Cite
|
Sign up to set email alerts
|

People’s explanatory preferences for scientific phenomena

Abstract: Previous work has found that people are drawn to explanations of psychological phenomena when these explanations contain neuroscience information, even when that information is irrelevant. This preference may be due to a general preference for reductive explanations; however, prior work has not investigated whether people indeed prefer such explanations or whether this preference varies by scientific discipline. The current study asked 82 participants to choose which methods would be most appropriate for inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
0
8
0
1
Order By: Relevance
“…One explanation would be that such evidence is considered a “better argument” (i.e., more satisfying or more impactful), thus rendering the defense’s argument more satisfying or impactful. This explanation seems likely because, outside of the legal arena, it has been consistently reported that people find neuroscience explanations of psychological phenomena more satisfying (i.e., the “seductive allure effect”; Hopkins et al, 2016; Weisberg et al, 2018, 2008, 2015). Subsequent studies have suggested that this is due to a general preference for reductive explanations across the sciences (Hopkins et al, 2016; Weisberg et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One explanation would be that such evidence is considered a “better argument” (i.e., more satisfying or more impactful), thus rendering the defense’s argument more satisfying or impactful. This explanation seems likely because, outside of the legal arena, it has been consistently reported that people find neuroscience explanations of psychological phenomena more satisfying (i.e., the “seductive allure effect”; Hopkins et al, 2016; Weisberg et al, 2018, 2008, 2015). Subsequent studies have suggested that this is due to a general preference for reductive explanations across the sciences (Hopkins et al, 2016; Weisberg et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This explanation seems likely because, outside of the legal arena, it has been consistently reported that people find neuroscience explanations of psychological phenomena more satisfying (i.e., the “seductive allure effect”; Hopkins et al, 2016; Weisberg et al, 2018, 2008, 2015). Subsequent studies have suggested that this is due to a general preference for reductive explanations across the sciences (Hopkins et al, 2016; Weisberg et al, 2018). However, of the studies reviewed herein, none asked mock jurors whether neuroscientific evidence is more satisfying, and only two asked mock jurors whether they found such evidence persuasive (Gurley & Marcus, 2008; LaDuke et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pseudoscientific neuro-jargon is particularly effective for psychological explanations in comparison with irrelevant social science and natural science jargon (Fernandez-Duque, Evans, Christian, & Hodges, 2015;Weisberg, Hopkins, & Taylor, 2018), perhaps due to the authority ascribed to neuroscience when explaining behaviour (Racine, Waldman, Rosenberg, & Illes, 2010).…”
Section: Epidemiology Of Pseudosciencementioning
confidence: 99%
“…Ilmu Pengetahuan Alam (IPA) atau Sains merupakan mata pelajaran yang tidak hanya dapat diperoleh dengan melihat dan membaca saja tetapi juga dalam konsepkonsepnya selalu berhubungan dengan berbagai fenomena alam dan fakta-fakta nyata yang berkaitan dengan gejala-gejala alam dalam kehidupan sehari-hari (Weisberg, Hopkins, & Taylor, 2018;Sudarmadji, 2013). Tujuan diberikannya materi IPA untuk peserta didik tingkat sekolah dasar yakni agar peserta didik dapat memahami konsep dasar Sains atau IPA yang kemudian dapat dihubungkan secara kontekstual dalam kehidupan sehari-hari (Erfan, Widodo, Umar, Radiusman, & Ratu, 2020).…”
Section: Pendahuluanunclassified